Tannin Extraction in Coconut Shell Powder (Cocodust) to Improve the Quality of Cocopeat and Obtain Tannin Products - Yuniwati, Murni; Munadatin; Kusmartono, Bambang; Yusuf, Muhammad (Engineering And Technology Journal, 2024)
Coconut, as a plant that is widespread in Indonesia, produces fruit pulp which has high potential to be developed as a valuable food raw material, as does coconut water. The meat and water in coconuts contain high calories, so more and more people are using them. However, the more consumption of coconut meat and water, the more waste in the form of coconut shells accumulates. One of the components of coconut skin is coconut husk powder (cocodust) which contains many macro and micro nutrients including N (Nitrogen), (K) Potassium, (P) Phosphorus, (Ca) Calcium, (Mg) Magnesium and several minerals. others that can fertilize plants. However, coconut shell powder also contains chlorine gas which causes an acidic atmosphere, and tannin compounds which interfere with plant growth because they block the absorption of nutrients by plants. The process of separating coconut husk powder from coconut skin is usually done by soaking the coconut husk in water, so that it becomes soft so that the coconut husk powder is easily separated. Apart from that, soaking in water is expected to reduce the acid and tannin content in the powder, but it turns out that the reduction in tannin content is not very significant. In fact, tannin is a very important compound that is used in the health sector as an antioxidant that can bind free radicals. Apart from that, tannin is widely used in industry as a leather tanner, dye, adhesive and so on. If we can extract tannin optimally, we will obtain two products that can be used, namely tannin as an antioxidant, and a high quality planting medium (cocopeat) because of the tannin content. becomes very small. In this research, tannin was extracted using an extraction method with various variables, to be able to determine optimal process conditions in order to obtain the maximum percentage of tannin extraction. The results of the research show that by using a water solvent under atmospheric conditions, the best conditions are obtained using a process temperature of 100oC, a stirring speed of 500 rpm, a ratio of solvent volume to mass of material is 10:1 and a process time of 1.5 hours. With these process conditions, the tannin content in the powder Coconut shells can be extracted perfectly, or the percentage of tannin extraction in coconut shell powder reaches 100%.